Pengaruh Matriks Pektin dan HPMC K15M Terhadap Daya Mengapung dan Mengembang serta Disolusi pada Tablet Floating Verapamil HCl dengan Metode Factorial Design - Ayuk Armadani , Valentina; Aisiyah, Siti; Kuncahyo, Ilham (Jurnal Farmasi (Journal of Pharmacy), 2020)
Verapamil HCl is Calcium Channel blocker (CCB) used to treat hypertension and angina pectoris. Verapamil HCl has a bioavailability of 10-20% and half-life of 4 hours so it can be made gastroretentive preparations for defending drug therapy concentration. This study was purposed to know the effect of pectin and HPMC K15M on floatation behaviour, swelling and drug released of verapamil HCl floating tablet. This study used four varying matrix concentrations of pectin and HPMC K15M with direct compression method then evaluated physical properties of powders and tablets. Effects and interactions between pectin and HPMC K15M were given by factorial design method using software Design Expert®. Matrix of pectin and HPMC K15M gave effects to floatation behaviour, swelling and drud released of verapamil HCl floating tablet. HPMC K15M was dominant influenced about decreased floating lag time and increased floating time. Increased of HPMC K15M and pectin could be decreased initial burst and drug released rate but increased swelling. Pectin and HPMC K15M (1,5:1) combination had the fastest of floating lag time, the longest time of floating time, the greatest of swelling and followed zero order.